Oral reactive capillary hemangiomas induced by SHR-1210 in the treatment of non-small cell lung cancer: a case report and literature review - Jinhan Zhou; Qinghua Mao; Yining Li; Zhiyong Li; Hong He; Qianming Chen; Chuanxia Liu (BMC, 2021)
Abstract Background Antibodies to PD-1 and PD-L1 have remarkably improved the overall survival of many patients with advanced solid tumors. SHR-1210 is an anti-PD-1 monoclonal antibody. Dermatologic reactive capillary hemangiomas (RCH) were the most common and unique drug-related AEs of SHR-1210, but rare on oral mucosa and gastrointestinal mucosa. Herein we report a case of RCH occurred in oral mucosa during the clinical trials of SHR-1210 in the treatment of non-small cell lung cancer. Case presentation A male in his 60 s with a history of non-small cell lung cancer received injection of anti-PD-1 monoclonal antibodies SHR-1210. The patient developed drug-related RCH on skin after the first injection and began to have gingival hyperplasia one year after the first injection which gradually increased in size and affect eating and speaking. Anti-PD-1 treatments were continued. After periodontal treatment, two oral lesions and one skin lesion were surgically removed. Similar histological manifestation was found in all three lesions as reactive capillary hemangiomas. All lesions had a good prognosis without recurrence on oral mucosa within one year after surgery. Conclusions Oral reactive capillary hemangiomas could be induced by SHR-1210 in the treatment of non-small cell lung cancer. Surgical resection is an effective treatment with a good prognosis.